Parent's Experience with and Desire to Use Complementary and Alternative Medicine After Stillbirth: Findings from an Online Survey - Sarah Fogarty; Jennifer Huberty; Phillipa Hay (Integrative Medicine Reports, 2022)
Objectives: Approximately 5.4 million parents worldwide are affected by stillbirth each year. There are limited therapeutic options for bereaved parents to manage their grief. A questionnaire was developed to learn more about parents' experience with complementary medicine after stillbirth. Design: An online questionnaire-based study was conducted. Setting: Australian and American parents, 18 years or over, and who had experienced a stillbirth in the past 36 months were recruited. The study was open for participation for 11 months. Main outcome measures: The authors developed the questionnaire based on existing survey instruments used for researching prenatal loss and complementary medicine. The complementary and alternative medicines included in the questionnaire include acupuncture, Ayurveda, biofeedback, Chinese Medicine, energy healing, exercise, homeopathy, massage therapy, meditation, mindfulness, naturopathy, Shamanism, tai chi, and yoga. The questionnaire included 43 questions in 5 sections: demographics, complementary medicine use over time, impact of the loss, preferences for coping with grief, and utilization of and experience of complementary medicine for coping with grief. Results: Almost 30% (29.8%) of respondents used complementary medicine to help manage their grief. Themes for how complementary medicine was perceived by help respondents included (1) helping them cope, (2) a self-care tool, and (3) a sense of control. The most popular complementary medicines used after a stillbirth were massage (n?=?36/72; 50%) and exercise (n?=?37/72; 51.4%). Respondents who used complementary medicine to help manage their grief had significantly slightly lower impact of event scale scores than those who did not use complementary medicine [r(213)?=??0.16, p?=?0.021). The study identified several barriers to complementary medicine use after a stillbirth, including not knowing much about it (n?=?85/103; 82.5%), cost (n?=?40/103; 38.8%), and a lack of confidence (n?=?23/103; 22.3%). Conclusions: The study found a desire for complementary medicine therapies to help manage grief especially massage and exercise.